Baska mask versus endotracheal tube in laparoscopic cholecystectomy: A prospective randomized trial / Mohammad Hafizshah Sybil Shah - Mohammad Hafizshah, Sybil Shah (2018)
Objectives: Evaluating the efficacy and safety of Baska mask as an alternative to endotracheal tube in patients undergoing general anaesthesia for laparoscopic cholecystectomy. Comparing the time to effective insertion, ventilatory performance, hemodynamic response and complications related to the airway. Methods: This is a prospective randomized controlled trial (RCT), single-blinded (patient) involving adult patients going in for laparoscopic cholecystectomy in the University of Malaya Medical Centre (UMMC), Kuala Lumpur. A total of 59 patients, age ranging from 18 ï¿½ 75 years old, ASA classification I to III were recruited in the study. Patients were randomized into two groups ï¿½ Baska mask and endotracheal intubation. Several parameters were evaluated intraoperatively ï¿½ time to effective airway insertion, time to orogastric tube insertion, ventilatory parameters and hemodynamic parameters. Immediate postoperative complications which include aspiration, laryngospasm, airway trauma and emergence cough were recorded. The incidence of sore throat, dysphonia, dysphagia, nausea and vomiting were recorded at 1 hour and 24 hours. Results: Baska mask showed significantly shorter time to insertion with high first attempt insertion rate. Orogastric tube insertion is faster with the Baska mask with lesser associated complications. The Baska group showed consistently high oropharyngeal leak pressure throughout and performed comparably like the endotracheal tube with regards to ventilation. Hemodynamic response during airway insertion was significantly lesser with the Baska mask. The incidence of emergence cough, sore throat and dysphonia was significantly lesser in the Baska group compared to the endotracheal tube group. Conclusion: The Baska mask is a suitable and safe alternative to endotracheal intubation in selected patients going for laparoscopic surgery. Key words: Baska mask, endotracheal tube, laparoscopic surgery